065 Septal DNETs rarely cause seizures – consider other causes. Issue 9 (12th August 2022) - Tanti, Matthew; Mullatti, Nandini; Sivakumar, Gnanamurthy; Warren, Daniel; Maguire, Melissa
Abstract : Dysembryoplastic neuroepithelial tumors (DNET) result in focal seizures. Septal DNET-like tumours however are only associated with seizures in 30% of cases. We report a patient with drug resistant epilepsy and another with functional seizures both with presumably incidental septal DNET-like tumours. A patient with semiology of temporal lobe epilepsy had a right sided 7.5 mm cystic lesion in keeping with DNET. His epilepsy was refractory so he underwent surgery workup. Video telemetry captured eight right temporal lobe seizures. To rule out ictal spreading starting from the septal lesion he had stereotactic EEG. This revealed seizure onset from the right lateral temporal lobe, and the septal lesion was electrically silent. He is waiting for a temporal lobectomy. A young patient presented with headaches and seizure like episodes. She was diagnosed with functional seizure. An initial MRI revealed high signal at the right temporal pole. Five years later she developed new sensory symptoms in the limbs and a repeat MRI revealed a new right DNET. Updated video telemetry captured numerous habitual events without evidence of electrical seizures. These cases support the notion that seizures due to septal DNETs are rare and that alternative seizure foci or diagnoses should be entertained.